BVES regulates c-Myc stability via PP2A and suppresses colitis-induced tumourigenesis. Issue 5 (14th January 2016) - Parang, Bobak; Kaz, Andrew M; Barrett, Caitlyn W; Short, Sarah P; Ning, Wei; Keating, Cody E; Mittal, Mukul K; Naik, Rishi D; Washington, Mary K; Revetta, Frank L; Smith, J Joshua; Chen, Xi; et al.
Abstract : Objective: Blood vessel epicardial substance (BVES) is a tight junction-associated protein that regulates epithelial-mesenchymal states and is underexpressed in epithelial malignancy. However, the functional impact of BVES loss on tumourigenesis is unknown. Here we define the in vivo role of BVES in colitis-associated cancer (CAC), its cellular function and its relevance to patients with IBD. Design: We determined BVES promoter methylation status using an Infinium HumanMethylation450 array screen of patients with UC with and without CAC. We also measured BVES mRNA levels in a tissue microarray consisting of normal colons and CAC samples. Bves −/− and wild-type mice (controls) were administered azoxymethane (AOM) and dextran sodium sulfate (DSS) to induce tumour formation. Last, we used a yeast two-hybrid screen to identify BVES interactors and performed mechanistic studies in multiple cell lines to define how BVES reduces c-Myc levels. Results: BVES mRNA was reduced in tumours from patients with CAC via promoter hypermethylation. Importantly, BVES promoter hypermethylation was concurrently present in distant non-malignant-appearing mucosa. As seen in human patients, Bves was underexpressed in experimental inflammatory carcinogenesis, and Bves −/− mice had increased tumour multiplicity and degree of dysplasia after AOM/DSS administration. Molecular analysis of Bves −/− tumours revealed Wnt activation and increased c-Myc levels. Mechanistically, we identified a new signalling pathway whereby BVES interacts with PR61α, a protein phosphatase 2A regulatory subunit, to mediate c-Myc destruction. Conclusion: Loss of BVES promotes inflammatory tumourigenesis through dysregulation of Wnt signalling and the oncogene c-Myc. BVES promoter methylation status may serve as a CAC biomarker.